2015
DOI: 10.3758/s13423-015-0921-5
|View full text |Cite
|
Sign up to set email alerts
|

Rare targets are less susceptible to attention capture once detection has begun

Abstract: Rare or low probability targets are detected more slowly and/ or less accurately than higher probability counterparts. Various proposals have implicated perceptual and response-based processes in this deficit. Recent evidence, however, suggests that it is attentional in nature, with low probability targets requiring more attentional resources than high probability ones to detect. This difference in attentional requirements, in turn, suggests the possibility that low and high probability targets may have differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Much of the work on this target probability effect has focused on unearthing its locus, with several proposals implicating perceptual (Dykes & Pascal, 1981;Jabar & Anderson, 2015;Lau & Huang, 2010;Menneer, Donnelly, Godwin, & Cave, 2010) and response stages (Fleck & Mitroff, 2007). Recently, though, the effect has been demonstrated to have an attentional locus (Hon, Ng, & Chan, 2016;Hon & Tan, 2013), with lower probability targets being disproportionately affected by attentional manipulations even when response and perceptual considerations were held constant. In many studies of the target probability effect, observers are not informed beforehand of the probability values used.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the work on this target probability effect has focused on unearthing its locus, with several proposals implicating perceptual (Dykes & Pascal, 1981;Jabar & Anderson, 2015;Lau & Huang, 2010;Menneer, Donnelly, Godwin, & Cave, 2010) and response stages (Fleck & Mitroff, 2007). Recently, though, the effect has been demonstrated to have an attentional locus (Hon, Ng, & Chan, 2016;Hon & Tan, 2013), with lower probability targets being disproportionately affected by attentional manipulations even when response and perceptual considerations were held constant. In many studies of the target probability effect, observers are not informed beforehand of the probability values used.…”
Section: Introductionmentioning
confidence: 99%
“…Selective attention makes modalities generate attention demands, and RSE will be affected by these attention demands (Pollmann & Zaidel, 1999). Studies have shown that the unimodal target probability can change attention demands (Hon et al, 2016; Hon & Tan, 2013), which may explain why MRE varies with unimodal target probabilities in modal-based selective attention. Overall, the modality dominance with modal-based selective attention and unimodal target probability manipulation can induce significant RSE.…”
Section: Discussionmentioning
confidence: 99%
“…Although questionable, we decided to include less noise stimuli in the NVA condition than target words in the VA condition to minimize the allocation of attention to word stimuli in the NVA condition. Indeed, it has been suggested that low-probability targets involve more attentional demands and are less sensitive to attentional capture compared with high-probability targets (Hon, Ng, & Chan, 2016;Hon & Tan, 2013).…”
Section: Experimental Paradigmmentioning
confidence: 99%